Supplementary abbreviated supine breast MRI following a standard prone breast MRI with single contrast administration: is it effective in detecting the initial contrast-enhancing lesions? - Aribal, Erkin; Bugdayci, Onur (TURKISH SOC RADIOLOGY, 2019)
PURPOSE We aimed to evaluate the detectability of contrast enhancing lesions, initially demonstrated in standard prone dynamic contrast-enhanced MRI (DCE-MRI), in a supplementary supine breast MRI examination performed following the standard prone DCE-MRI examination and to show the correlation of spatial displacement of the lesions with breast size and density. METHODS Forty-two patients with 45 lesions were prospectively evaluated. Supine breast MRI was acquired with a 6-channel body coil following a standard DCE-MRI in prone position after repositioning the patient. No additional contrast media was administered. Images were evaluated by two radiologists in consensus for the visibility of the lesions. Lesion localization relative to the sternal midline, chest wall and nipple was measured in both prone and supine positions. Correlations between lesion displacement and breast size or breast density were analyzed. RESULTS Of 45 lesions, 23 (52.3\%) were masses, 22 (47.7\%) were nonmass enhancements (NME). Forty-four lesions (97.8\%) could be detected on supine images. One linear NME of 33 mm in length could not be seen on supine images. Twenty (46.5\%) of the detected lesions in supine position were equal to or smaller than 10 mm (11 NME {[}55\%] and 9 masses {[}45\%]). Lesion displacement relative to the chest wall increased with increasing breast size (P < 0.001). CONCLUSION An abbreviated supine sequence following a standard prone DCE-MRI with single contrast media administration is an effective method for defining the lesion location in supine position.